Analysis of composite box beam with piezoelectric actuators using ANSYS - Syed Mohamed Ali, Jaffar; Shaik Dawood, Mohd. Sultan Ibrahim; Syed Muhammad, Kashif; Tariq, M. (2013)
In this work the potential of piezoelectric actuators to induce twist on a composite helicopter rotor blade has been investigated using ANSYS. An analogical thin-walled box beam has been modeled to investigate the effects of different ply orientations, boundary conditions and applied loads on displacement and twist of the box beam. Results obtained confirm piezoelectric actuators can be effectively used for the said purpose. Significant influences of boundary conditions and ply orientations were observed on the deformation and twist output. Although the studies were carried out on a simple box beam model, the output from this work could serve as a useful reference for future work.